Russian University Cities: Expectations vs. Reality - I. D. Turgel; K. D. Bugrov; A. D. Oykher (Высшее образование в России)
This article proposes an approach to the analysis of the role of universities in the socioeconomic ecosystem of their host city, which makes it possible to pinpoint the specifics of the university city phenomenon in modern Russia. The study uses the theory of functional specialization of complexly organized spatial systems as its underlying methodology. To address specific research questions, methods of comparative, evolutionary and economic-statistical analysis are used. As a result of the study, the authors establish the specifics of the spatial distribution of universities in Europe, the USA and the Russian Federation; and substantiated the choice of Tomsk, Novosibirsk and Yekaterinburg as the relevant research sample for the Russian Federation. The article proposes the methodology for assessing the role of universities in the socio-economic space of the city comprising: a set of calculated economic and statistical indicators; analysis of the established practice for deciding if to represent a particular city as a scientific and educational center in strategic management directives; and integral interpretation of the results obtained. The analysis of the leading scientific and educational centers in Russia stated above indicates that in no city the share of the university sector in the overall number of the city’s employees, or its population, reaches 20%–the key threshold for establishing the predominance of universities in the functional the structure of a city. At the same time, the economic dominance of Tomsk universities in their city (the total income of Tomsk universities exceeds the city’s budget, which is unique for Russia) became the basis for positioning the city as the “student capital city” of the country. Yekaterinburg and Novosibirsk, which exceed Tomsk in absolute terms, such as number of universities and total number of students studying in the city, lag Tomsk in the sphere of symbolic representation. The article concludes that, due to the specifics of its genesis and evolution, the phenomenon of a university city in Russia receives a new significance, reflecting the diversity of relationships between a large city and a complex, hierarchical system of universities operating in the socio-economic space of a common territory.